Kingella kingae Causing Septic Arthritis of the Knee in an Immunocompetent Adult. (14th June 2015) - Ricketts, J.; Rehmatullah, N. N. T.; Sutton, P.
Abstract : The bacterium Kingella kingae is a species of Gram-negative coccobacillus usually found in the oropharynx. This is an emerging pathogen reported to cause bacteraemia, endocarditis, and osteoarticular infections in children and endocarditis in the immunocompromised adult. However, there are few cases of isolated joint infections reported in the immunocompetent adult. Due to specific isolation techniques required, delay in diagnosis can compromise patient outcome. We report a rare case of septic arthritis of the knee in an immunocompetent adult caused by K. kingae .